The reality of the relationship between the dimensions of social capital and the quality of educational service. In the Kurdistan Region - Iraq: Analytical study - Ahmed , Parwin; Abdullah, Aso (Al-Adab Journal, 2024)
Social capital is one of the resources inherent in the social structure that can be accessed and used for intentional actions; therefore, these resources, along with material and human resources, in educational institutions contribute to improving the quality of educational service. One of the research problems is the lack of realization of the importance and role of these resources by the workers in educational institutions, and one of its importance is the introduction of social capital as social resources in the process of education, The research aims to know how to invest the dimensions of social capital and its relationship to indicators of the quality of educational service in the Ministry of Education in the Kurdistan Region of Iraq.     Social capital consists of a set of dimensions including-: social networks, social relations, social trust, social interaction and exchange, social values, and standards. These dimensions act as independent variables and are related to indicators of the quality of educational service, which include factors such as the educational system, curricula, teaching methods, assessment and examinations, student satisfaction, abilities and skills, educational attainment, educational democracy, and social equality, as dependent variables in the process. By investing in the dimensions of social capital that contribute to the provision of non-material resources for educational institutions, it is possible to improve the quality of educational service. A significant discovery of a research study was that the Ministry of Education in the Kurdistan Region of Iraq has objectives, philosophy, and activities that demonstrate the correlation between each dimension of social capital and indicators of the quality of educational service.